A Critical Review on Corrosion and its Prevention in the Oilfield Equipment - Kadhim, Mothana Ghazi; Ali, Dr. Mushtaq Taleb (Journal of Petroleum Research and Studies, 2017)
Corrosion in the petroleum industry is one of the crucial failure has to take in consideration in the design of the oilfield equipment due to not only reducing economic losses but also to safe and protect the resources. Thus, various experimental and numerical studies were performed to understand the mechanisms and rules of corrosion types occurred in the oil and gas production fields and determine the factors affecting these types. The current investigation is aimed to comprehensively review different types of corrosion took place in the oilfield and flow line equipment and how they can be prevented. The effect of diverse harsh working environmental representing by the existence of high content of corrosive gases (e.g., carbon dioxide (CO2)and hydrogen sulfide (H2S)) is also considered. Additionally, different types of protection methods used to prevent the corrosion or at least reduce the corrosion rate including inorganic inhibitors (e.g., anodic and cathodic protection methods), organic inhibitors (e.g., film former or coating) and maintain the environmental conditions (e.g., scavengers and biocides) are considerably presented.